صوفیاے کرام اور متصوفین کا تصورِ علم: کشف المحجوب کی روشنی میں ایک مطالعہ: Concept of Knowledge According to Sufis and Mutaswwifīn: A Study in the Light of Kashf al-Mahjūb (Al-Qamar, 2022)
The study is on concept and thoughts of Saints and so-called Saints of knowledge. The analysis of Saints and So-called Saints’ thoughts and their definitions have been given in the essay. Saint is devotee of knowledge, and bears hardships and difficulties willingly for the sake of seeking knowledge. The basic condition for becoming saint is to seek knowledge. Saints’ knowledge helps to get Allah’s willingness and the target of it is to have recognition of Allah. Saint considers knowledge and action complementary for each other and saves his energies and stocks to spend on objectiveless and profitless knowledge. He becomes loving to Allah due to its intrinsic and extrinsic benefits. However, so called saint always targets his personal and material benefits. He prospers his life on the name of his predecessors. A lot of difference is found in the character and objectives of both partners. The person, who is embodiment of knowledge and follows the character of his predecessors, deserves to be a religious guide for Allah’s creation. Therefore, saints remained away from the so-called saints, bad scholars, and claimant of Allah’s recognition without piety.
Keywords: Offensive women; Islam; Society; Socialization; Parents; Social Exclusion; Offensive behavior; factors; consequences; leisure; poor law and disorder; State; Human rights; Unemployment